2021
DOI: 10.1021/acs.analchem.1c01497
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Chiral CuO/CoO Nanofibers: An Enhanced Electrochemiluminescence Sensing Strategy for Detection of 3,4-Dihydroxy-Phenylalanine Enantiomers

Abstract: l-3,4-Dihydroxy-phenylalanine (l-DOPA) is the most effective drug for the treatment of Parkinson’s disease, which plays a very important role in clinical and neurochemistry. However, how to achieve high-sensitivity recognition of l-DOPA still faces challenges. Here, a facile strategy is presented to construct nitrogen-doped chiral CuO/CoO nanofibers (N-CuO/CoO NFs) with nanozyme activity and electrochemiluminescence property, in which CuO/CoO NFs are used as the catalytic activity center and chiral cysteine (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Nitrogen‐doped chiral CuO/CoO nanofibers were prepared as POD‐like nanozymes with an electrochemiluminescence (ECL) property. This D‐cysteine (Cys)‐modified nanozyme exhibited varying ECL performances in the presence of dihydroxyphenylalanine enantiomers (Song et al., 2021).…”
Section: Mechanisms Of Nldsmentioning
confidence: 99%
“…Nitrogen‐doped chiral CuO/CoO nanofibers were prepared as POD‐like nanozymes with an electrochemiluminescence (ECL) property. This D‐cysteine (Cys)‐modified nanozyme exhibited varying ECL performances in the presence of dihydroxyphenylalanine enantiomers (Song et al., 2021).…”
Section: Mechanisms Of Nldsmentioning
confidence: 99%
“…However, in previous studies, CoO nanoparticles have often been doped with other substances as part of the catalyst. Few studies have used CoO nanoparticles alone as catalysts to participate in the reaction, and most of the related enzyme-like catalytic activities were peroxidase-like or oxidase-like [53][54][55][56]. In this paper, we prepared CoO nanoparticles with a "cluster" morphology, and the morphology of CoO nanoparticles can be changed by changing the reaction temperature.…”
Section: Relieve the Pathological Symptoms Of The Ear Skin Of Ad Micementioning
confidence: 99%
“…Co 3 O 4 nanozymes are widely used in cancer therapy, antiviral, magnetic resonance imaging (MRI), and targeted drug delivery [49][50][51]. At present, many studies have reported that CoO nanozymes with POD-like activity prepared by a variety of synthetic methods have extremely high application value in biosensing [52][53][54][55]; CoO nanostructures have the advantages of high stability, large specific surface area, and easy redox [56,57]. However, pure CoO nanoparticles show poor electrical conductivity and tend to self-aggregate to cover active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Nanozymes with oxidase/peroxidase activity play a critical role in the oxidation reaction of colorless TMB to blue ox-TMB. So far, the reported nanozymes mainly include carbon-based nanomaterials (for example, graphene oxide, carbon nanotubes, , and carbon nanodots), metals (such as Au, , Pt, Ag, and Ni), metal oxides (such as CeO 2 , MnO 2 , CuO, and Mn 3 O 4 ), and other nanocomposites (such as Co 3 O 4 @CeO 2 , TiO 2 @CeOx, NPG/Cu 2 O, and magnetic nanoporous graphene). Among them, nanocomposites exhibit excellent catalytic performance due to their strong synergistic effect and rich hybrid connection with redox relationships .…”
Section: Introductionmentioning
confidence: 99%